(3efXheI aj Yde GdefWbs - (3YHO GdYRjR GdecfGSj GdaGSjs ((3CMeO Hf edG eMeO GdTGaYi GdMUcai s)
(3ChdgG (B:s
(3hHYO aGdYde Chd eG Hg ETJZdG Ph geI HYO aQV GdhbJ Ef fRdG s
(3BNQgG (B:s
(3HGdMeO Hg ai NJe hcd MGd ef GdCMhGd EP cdgG JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B8s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQGJ GdCUd (B:s
(3bQFJ Ydi GdeDda SfI (B951 (3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3GdeLGejYs